2024
DOI: 10.1002/agr.21935
|View full text |Cite
|
Sign up to set email alerts
|

Does urban–rural integration reduce rural poverty?

Kunzai Niu,
Hengzhou Xu

Abstract: Rural poverty reduction is a challenge worldwide. Urban–rural integration is not only the result of urban and rural development but also the cause of poverty alleviation. Few studies, however, have used empirical methods to examine the social impact of urban–rural integration. Against the Chinese background, this study adopts an empirical method to analyze the impact of urban–rural integration on rural poverty reduction at the micro level. The study finds that urban–rural integration can reduce rural household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Above all, the existing literature has predominantly focused on the externalities of land transfer [84,85], poverty reduction mechanisms [86][87][88], and market mechanisms among farmers [89,90]. Wu et al conducted a study using data from 2011 to 2014 in rural China, which revealed that farmer participation in land transfer led to a significant reduction in fertilizer application intensity in a grain-growing region in Western China [91].…”
Section: Impact Of Land Transfer Behavior (Str) On Farmers' Livelihoo...mentioning
confidence: 99%
“…Above all, the existing literature has predominantly focused on the externalities of land transfer [84,85], poverty reduction mechanisms [86][87][88], and market mechanisms among farmers [89,90]. Wu et al conducted a study using data from 2011 to 2014 in rural China, which revealed that farmer participation in land transfer led to a significant reduction in fertilizer application intensity in a grain-growing region in Western China [91].…”
Section: Impact Of Land Transfer Behavior (Str) On Farmers' Livelihoo...mentioning
confidence: 99%